2020
DOI: 10.3390/agronomy10122006
|View full text |Cite
|
Sign up to set email alerts
|

A New Diversity Panel for Winter Rapeseed (Brassica napus L.) Genome-Wide Association Studies

Abstract: A diverse population (429 member) of canola (Brassica napus L.) consisting primarily of winter biotypes was assembled and used in genome-wide association studies. Genotype by sequencing analysis of the population identified and mapped 290,972 high-quality markers ranging from 18.5 to 82.4% missing markers per line and an average of 36.8%. After interpolation, 251,575 high-quality markers remained. After filtering for markers with low minor allele counts (count > 5), we were left with 190,375 markers. The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Thermo Fisher Scientific). The GBS library was constructed using the same protocol described in Horvath et al (2020). The GBS library was sequenced on an Illumina (San Diego, CA) HiSeq 4000 to generate single-end, 100-bp reads at the Genomic Sequencing and Analysis Facility at the University of Texas Southwestern Medical Center at Dallas, TX.…”
Section: Snp Marker Discovery and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermo Fisher Scientific). The GBS library was constructed using the same protocol described in Horvath et al (2020). The GBS library was sequenced on an Illumina (San Diego, CA) HiSeq 4000 to generate single-end, 100-bp reads at the Genomic Sequencing and Analysis Facility at the University of Texas Southwestern Medical Center at Dallas, TX.…”
Section: Snp Marker Discovery and Genotypingmentioning
confidence: 99%
“…Local LD decay rates for 500 Kb with a 10 Kb sliding window was determined based on the method done previously (Horvath et al, 2020) to produce an LD decay In total, 69,554 SNP markers were identified for the 222 accessions with missing values less than 50%. Model-based cluster analysis suggested that there were eight subgroups (Figure 2 and Table S1, spreadsheet "Class and Country of origin"); there was no clear relationship between geographic distribution and the subgroups.…”
Section: Selection Of Potential Candidate Genesmentioning
confidence: 99%
“…The most significantly associated marker (S1_750314091) maps to position 37,666,286 on chromosome Ann_random from the B. napus reference assembly [15]. This region of the genome has a fast linkage decay rate with loss of linkage occurring within 100 bases in this population [16]. There are no known B. napus gene models within this narrow region, but the marker does fall in the middle of a characterized EST (DMBras.unigeneT00180796001).…”
Section: Gwas Identified Multiple Loci Associated With Freezing Toler...mentioning
confidence: 99%
“…A well-characterized diversity panel of primarily winter B. napus varieties [16] composed of 397 varieties was used in this studied. Briefly, this population is diverse with a minimal population structure with a K vs. Ln likelihood plot showing a drop between K-values of 2 and 4 and a neighbor-joining tree indicated as few as 6 major branches.…”
Section: Genome-wide Association Studymentioning
confidence: 99%
See 1 more Smart Citation